Porous Ceramic Matrix Al2O3/Al Composites as Supports and Precursors for Catalysts and Permeable Materials - Pakhomov, Nikolai; Nemykina, Elena; Salanov, Aleksey; Sadykov, Vladislav; Romanenkov, Vladimir; Pietiushyk, Tatiana; Tikhov, Serguei (IntechOpen, 2011)
None